Kedudukan Hukum antara Dokter, Perawat dan Rumah Sakit dalam Memberikan Pelayanan Kesehatan kepada Pasien di Indonesia - Basri, Hasan; Risdawati, Irsyam; Sidi, Redyanto (LPPM Institut Pendidikan Nusantara Global, 2025)
The existence of doctors and nurses or other health professionals in hospitals in the implementation of health services must be able to realize the highest degree of health for the community, integrated and comprehensive health efforts are carried out in the form of individual health efforts and public health efforts. This certainly makes it interesting to discuss the legal position of doctors and nurses as implementers of health services in hospitals, and the legal position of hospitals as places where health services are implemented. This study uses the theory of legal protection so as to obtain results where the legal position of doctors and nurses as implementers of health services and as parties who provide treatment to people who need it, while the legal position of hospitals as a place where health services are implemented or as a place for patients who receive health services which in this case is carried out by medical personnel, specifically doctors and nurses and the position of patients as the party who needs health services, where this relationship is a very personal relationship because it is based on the trust of the patient in the doctor which is called a therapeutic transaction while the nurse in the medical action carried out by the doctor is based on the delegation of authority regulated by law.